Majmūʻah baḥs'hā dar zamīnah-'i shinākht, hidāyat va tarbiyat-i nawjavānān va javānān - Qāʼimī, ʻAlī (Intishārāt-i Amīrī, 1985)
On the education and upbringing of the youth based on Islamic teachings in contemporary Iranian society.